Владигор. Маска Владигора: [роман] / Сергей Карпущенко - Карпущенко Сергей Васильевич (АСТ, 1999)
Экземпляры: АБ (20170109) / Инвентарный номер: 32899 / Цена: 23.40 / Сис.шифр: Р2 / Авт.знак: К 26 / ГРНТИ: 17.82.31 / ББК: 84